DETERMINATION SOME OF COMPLEMENT COMPONENTS IN INFERTILITY WOMEN WITH ANTISPERM ANTIBODIES (Iraqi Journal of Medical Sciences, 2016)
Background: Classical activation of complement by antigen and antibody complex leads to formation of membrane attack complex (MAC) that leads to formation holes on the spermatozoa ending in their destruction. Objective: To determine the complements levels and antisperm antibodies in the sera of infertile women of unknown etiology.Patients and methods: Study group consisted of 45 infertile women consulting Kammal El-Sammarei Hospital for Infertility and In Vitro Fertilization from Jun -2008 to June-2009. Twenty-four (53.3%) patients had primary infertility and the rest had secondary infertility. Control group: consisted of thirty fertile women. Blood samples were collected from them and anti sperm antibodies in the serum were detected by indirect immunofluorescence test (EURO IMMUNE –GERMENY). In addition to that serum were tested for complement levels (C3 and C4) using single radial immune diffusions test (BINDARID) KIT BIRMINGHAM .UK.Results: Detections of antisperm antibodies in the serum of infertile women were (64.4%) which is significantly (p
Keywords: Infertility; antisperm antibody; complement